ROLE OF SENSORY CONFLICT IN FORMING OF HEALTH DISORDERS IN EMPLOYEES EXPOSED BY PHYSICAL FACTORS - V. A. Pankov; V. S. Rukavishnikov; N. V. Kartapoltseva; M. V. Kuleshova; D. V. Rusanova (Acta Biomedica Scientifica, 2012)
The article presents the results of the study of psychological status, centra! and peripheral nervous systems, neuromuscular apparatus in patients with vibration-induced, disease and sensorineural deafness of occupational genesis. The dynamics of forming of changes in these systems with the increase of vibration and. noise doses in the experiment on laboratory animals is showed. The results allowed, to supplement and. extend, the ideas about the conception of «sensory conflict».